2005
DOI: 10.1213/01.ane.0000166764.99863.b4
|View full text |Cite
|
Sign up to set email alerts
|

Hemodynamic Responses to Etomidate on Induction of Anesthesia in Pediatric Patients

Abstract: Etomidate is often used for inducing anesthesia in patients who have limited hemodynamic reserve. Using invasive hemodynamic monitoring, we studied the acute effects of a bolus of etomidate during induction of anesthesia in children. Twelve children undergoing cardiac catheterization were studied (mean age, 9.2 +/- 4.8 yr; mean weight, 33.4 +/- 15.4 kg); catheterization procedures included device closure of secundum atrial septal defects (n = 7) and radiofrequency catheter ablation procedures for supraventricu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
52
2
2

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(58 citation statements)
references
References 18 publications
2
52
2
2
Order By: Relevance
“…[ Table 4] DISCUSSION: Etomidate has been compared to other induction agents in various studies and has been known to preserve the haemodynamics whereas propofol does not. 8,9,10,11 Various mechanisms are proposed for these differences in haemodynamic response of these drugs. Propofol has been shown to decrease preload, 12 afterload, 13 and myocardial contractility.…”
Section: Resultsmentioning
confidence: 99%
“…[ Table 4] DISCUSSION: Etomidate has been compared to other induction agents in various studies and has been known to preserve the haemodynamics whereas propofol does not. 8,9,10,11 Various mechanisms are proposed for these differences in haemodynamic response of these drugs. Propofol has been shown to decrease preload, 12 afterload, 13 and myocardial contractility.…”
Section: Resultsmentioning
confidence: 99%
“…It is short acting drug, used for induction and maintenance of anesthesia [7]. The most important side effects of Etomidate are nausea and vomiting that may lead to aspiration in patients [8][9][10]. Intravenous Injection of Etomidate would cause a burning sensation.…”
Section: Introductionmentioning
confidence: 99%
“…One of the most important, but rare side effects of this drug is the suppression of steroids production by reversible inhibition of 11betahydroxylase enzyme [10,11]. Induction of anesthesia by Etomidate would lead to a stable hemodynamic condition for performing laryngoscopy and endotracheal intubation [9,10,12].…”
Section: Introductionmentioning
confidence: 99%
“…Weisenberg M et al found in their study that the mechanisms of arterial hypotension following IV anesthetic induction were multifactorial. The hemodynamic stability seen with etomidate may be due to its unique lack of effect on both the sympathetic nervous system and baroreceptor function and capacity to bind and stimulate peripheral alpha-2B adrenergic receptors with a subsequent vasoconstriction 3 . Decrease in systemic blood pressure after bolus injection of propofol is dependent on both vasodilation with reduced preload and after load and myocardial depression (negative inotropic action).…”
Section: Discussionmentioning
confidence: 99%